ВРЕМЕННОЙ СПЕКТР КОЛЕБАНИЙ УРОВНЯ ЧЕРНОГО МОРЯ И ЕГО ВОЗМОЖНАЯ СВЯЗЬ С ДИНАМИКОЙ ИЗМЕНЕНИЯ ПОЛОЖЕНИЯ РТ-22 КРАО КАК ЭЛЕМЕНТА ЕВРОПЕЙСКОЙ ГЕОДИНАМИЧЕСКОЙ РСДБ СЕТИ - Рябов, М. И.; Вольвач, А. Е.; Сухарев, А. Л.; Донских, А. И.; Адобовский, В. В.; Куклина, Н. Я.; Шабалина, О. А.; Губарь, Г. А.; Покидайло, С. Л. (Одеські астрономічні публікації, 2011)
Using the international geodynamic VLBI program during 1994-2010 years the coordinates of the station "Simeiz" are determined. The results of measuring of RT-22 Simeiz coordinates with the monthly averages of the data long-term measurements of the Black Sea level stations, located in Odessa, Ochakov, Sevastopol, Yalta and Katsively are estimated. All items of sea level measuring have a different water flow, which gives the opportunity to explore global geodynamic processes and their dependence on solar activity cycle. The spectrum of sea level variations in different points indicates the presence the periods of one to 11 and 22 years. Using wavelet analysis the periods for each level station separately are estimated.